Peningkatan Hasil Belajar Peserta Didik Konsep Pra Aksara Melalui Strategi Digital Pre-Historic Assesment - Endang Winih Prasetyaningrum (Jurnal Didaktika Pendidikan Dasar, 2020)
The study entitled "Improving Student Learning Outcomes Class VII.B Pre-Literacy Concepts Through Digital Pre-Historic Assessment (DIPHA) Strategy" aims to find out Dipha's strategy can improve pre-literacy concept learning outcomes as well as to find out how much the achievement of learning material increases pre-literacy in grade VII students. B Ummu'l Quro Middle School Depok. This research is a classroom action research in class VII.B as many as 23 students for two cycles. Each cycle consists of two meetings. Based on the data obtained, learning using the Dipha strategy can improve learning outcomes. This success was marked by an increase in student learning outcomes including increasing mastery learning in attitude assessment by 33%, knowledge assessment by 91%, and skills by 74%, the average test increased from 69% to 91%. From the data acquisition and discussion, it can be concluded that Dipha's strategy can improve the learning outcomes of grade VII.B students of SMP IT Ummu'l Quro Depok on the pre-script concept.